New U-Pb zircon ages of El Baúl Massif, Cojedes State, Venezuela. - Viscarret, Patxi; Wright, James; Urbani, Franco (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
El Baúl massif (Cojedes State, Venezuela) has been studied since 1858, especially as an important target for oil companies since it is a structural high that has played an important role in the evolution of the oil bearing Barinas-Apure and Eastern Venezuela sedimentary basins. In addition, igneous and metamorphic rocks have received attention to understand the evolution and relationships of the granitic bodies and their enveloping rock. Prior to this study the Mogote Granite was considered Permian, based on two ages of 287 Ó 10 Ma Rb/Sr and 270 Ó 10 Ma K/Ar, while the Guacamayas volcanics, were considered Early Jurassic, also for two K/Ar ages (192 Ó 3.8 Ma and 195 Ó 3.9 Ma). Due to the currently known unreliability of these ages obtained decades ago, new work was done where five new U-Pb zircon ages, in the granitic and volcanic rocks were obtained with the SHRIMP-RG method. The new ages are: El Corcovado Rhyolite, 286.4 Ó 2.8 Ma and La Segoviera Rhyolite, 283.3 Ó 2.5 Ma (Early Permian), both of the Guacamayas Super Suite. For El Baúl Granitic Suite were obtained ages for: Piñero Granite (289.0 Ó 2.9 Ma) and Mata Oscura Granite (294.1 Ó 3.1 Ma), both Early Permian, whereas the Mogote Granite (493.8 Ó 5.2 Ma) is Late Cambrian. These new ages show that the El Baúl massif forms part of an igneous and metamorphic Paleozoic belt, with features more similar to the known geology of the Merida Andes and the Coastal mountains than to the Guyana Shield as previously postulated. Besides it does not appear to behave as an “Arch“spreading from the Guyana Shield up to the Paraguaná peninsula, as previously thought.